REPRESENTASI DEPRESI DALAM FILM AFTERSUN (The Commercium, 2023)
Film is a mass communication medium that describes the social reality that occurs in society. Representation is the use of signs displayed through audio-visual or other means to describe something that can be accepted by the five human senses. Representation of film is a process of giving meaning to the symbols or signs in it in order to understand more deeply the message to be conveyed in the film. This research aims to focus on discussing the representation of depression in the film Aftersun because depression is still a taboo topic to discuss even though depression is a major contributor to the overall global disease, especially during the Covid-19 pandemic and beat cancer for the first time. This research takes a descriptive qualitative approach by using Charles Sanders Peirce's semiotic theory as an analytical knife and dividing the analysis into Peirce's trichotomy. The data used in this research are scenes from the film Aftersun where there are elements related to the representation of depression. The results of this study show that the film Aftersun depicts depression by showing Calum's vulnerability as a man and also as a father who breaks the stigma of masculinity of depressed men.